Chance taken - Bourne, Lena (knjige, 2022)
Veronica. Five years ago, my sister was abducted by an outlaw biker club. I failed to protect her, so I devoted my entire life to bringing her captors to justice. I have it narrowed down to only one club who could’ve done it–-Devil’s Nightmare MC. I am certain they are the ones who abducted my little sister all those years ago. So when one of their members gets assigned community service at the foundation I run to help sex trafficking victims, I'm sure I'll finally get the justice I seek. But he’s nothing like the monster I know he must be. He’s friendly and charming and infuriatingly attractive. And he says and does exactly the right things at exactly the right times. But I will not fall for his gorgeous blue eyes and sweet words. They’re all lies. Problem is, that might not be as easy as it sounds. /// Chance. One wrong decision and now I have a year of community service to attend, and the thorny path back into my MC’s good graces to walk. Being the VPs son won’t help me now, not that I wish it would. I gotta earn my brothers’ trust on my own. As for the community service, I was sure at least that much had gone my way when I first laid eyes on my beautiful “warden”, Veronica. Not so much. She looks like a goddess, but acts like one of the furies. She’s got it in her head that I helped kidnap and sell her little sister. As if. But nothing I can say or do works to convince her otherwise. The harder she pushes me away, the more I want her. I’ve never met a woman like her before. And now that I have, no other woman will do.